Defining the Next 2-5 Years Training & Development Programs: A Case of NBTC Thailand - Srisuphol, Jirayu; Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This qualitative research comprises two objectives: 1. to explore the insights of key informants (e.g., Senior-level officer, Mid-level officer, and officer) on the next 2 – 5 years’ training and development programs for NBTC, an d 2. to propose the next 2 – 5 years’ training and development programs for NBTC based on the content analysis of the interview passages. The research site is the Office of The National Broadcasting and Telecommunications Commission (Office of NBTC) main headquarters in the Phaholyothin Road area. The population is full-time employees of the Office of NBTC, who oversee every cluster of NBTC (Broadcasting Cluster, Administration Cluster, Telecommunications Cluster, Regional Affairs Cluster, and Strategic and Internal Affairs Cluster), while the actual key informants comprise 30 persons. The research instrument employed in this study is in-depth interview questions. The findings from the contents analysis inter-coding process revealed ten themes, consisting of 1) Basic knowledge, 2) Mission and Vision, 3) New Technologies, 4) Working Technique, 5) Term of Reference (TOR), 6) meeting minutes, 7) Online Class, 8) Leadership, 9) Critical thinking, and 10) Systematic thinking & Strategic Planning. The conclusion is that the top three priorities for the next 2-5 years of training & development programs are in the areas of 1) Basic knowledge, 2) Term of Reference (TOR), and 3) Mission and Vision and New Technologies. Recommendations are presented by orders of the officer-level, middle-level, and senior-level roles, with details provided in the following part of this paper